Can Foreign Investment In Real Estate Improves Host Country's Affordability? - Masron, Tajul Ariffin; Zull Kepili, Ema Izati (Asian Academy of Management (AAM), 2016)
Inflows of foreign capital are necessary to complement the available domestic fund or capital of host countries. Foreign capital may also bring in management skills, latest technology and so on, which later has the potential to be transferred to local firms in host countries. It is expected that foreign capital will elevate host country's affordability. Nonetheless, this argument is very much one-way. Foreign capital is also expected to be able to exert negative consequences such as fuelling up domestic price (either stock market price, and/or real estate price) and failure to effectively transferring knowledge, skills and technologies, leading to unchanged or lower country's affordability level. Hence, this study aims at investigating the effect of foreign investment in real estate (FIRE) on host country's affordability. Using 30 emerging markets as a case for the period of 2000–2011, estimated by using fixed-effect model and complemented by 2-stage least square (2SLS) method, this study found that FIRE has a tendency to generate positive effect on countries' affordability. On the policy implication side, government can continue attracting foreign investment in real estate but it should be done cautiously as the effect is not elastic.